1997
DOI: 10.1128/aem.63.5.1749-1755.1997
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Is Not Required for Biobleaching of Oxygen-Delignified Kraft Pulp by the White Rot Fungus Bjerkandera sp. Strain BOS55

Abstract: The white rot fungus Bjerkandera sp. strain BOS55 extensively delignified and bleached oxygen-delignified eucalyptus kraft pulp handsheets. Biologically mediated brightness gains of up to 14 ISO (International Standards Organization units) were obtained, providing high final brightness values of up to 80% ISO. In nitrogen-limited cultures (2.2 mM N), manganese (Mn) greatly improved manganese-dependent peroxidase (MnP) production. However, the biobleaching was not affected by the Mn nutrient regimen, ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…Moreover, paper pulp bleaching by Bjerkandera sp. has been described, suggesting that there is an Mn-independent activity (18). In the present study, dye decolorization in the absence of Mn 2ϩ was also obtained with P. eryngii MnP isoenzymes but not with P. chrysosporium MnP1, suggesting that the Pleurotus and B. adusta enzymes may form a subclass of MnP isoenzymes that oxidize both Mn 2ϩ and a variety of aromatic compounds.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, paper pulp bleaching by Bjerkandera sp. has been described, suggesting that there is an Mn-independent activity (18). In the present study, dye decolorization in the absence of Mn 2ϩ was also obtained with P. eryngii MnP isoenzymes but not with P. chrysosporium MnP1, suggesting that the Pleurotus and B. adusta enzymes may form a subclass of MnP isoenzymes that oxidize both Mn 2ϩ and a variety of aromatic compounds.…”
Section: Discussionsupporting
confidence: 53%
“…strain BOS55 showed that MnP isoenzymes were produced in the absence of Mn and that these were distinguished from the LiP isoenzymes. The LiP isoenzymes were incapable of Mn(I1) oxidation [24,28].…”
Section: Discussionmentioning
confidence: 99%
“…Using a modified method of Moreira et al [10], 50 g of OKP (ISO brightness 52%, kappa number 8.5, Mn concentration 20.1 mg/kg pulp) was immersed in 2 l of 5 mM EDTA at room temperature for 12 h to remove Mn ions. The pulp was washed with water, and dried at room temperature to give manganese-less OKP (E-OKP; Mn concentration <0.1 mg/kg pulp).…”
Section: Edta Treatment Of Oxygen-delignified Hardwood Kraft Pulpmentioning
confidence: 99%
“…Unbleached hardwood kraft pulp (HWKP) contains Mn at a concentration of about 50 mg/kg pulp [6,9], and P. sordida YK-624 utilizes Mn during the biobleaching of HWKP because this fungus can produce MnP and brighten HWKP in a culture containing only HWKP and water [5,6]. However, Moreira et al [10] found that the white-rot fungus Bjerkandera sp. BOS55 extensively delignified and bleached oxygen-delignified hardwood kraft pulp (OKP) without the requirement of Mn.…”
Section: Introductionmentioning
confidence: 99%